2019
DOI: 10.48550/arxiv.1909.13532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Maximum Number of Pentagons in a Planar Graph

Abstract: Hakimi and Schmeichel considered the problem of maximizing the number of cycles of a given length in an n-vertex planar graph. They determined this number exactly for triangles and 4cycles and conjectured the solution to the problem for 5-cycles. We confirm their conjecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Also, it is straightforward to see that the complete bipartite graph K 2,n−2 contains 1 2 (n 2 − 5n + 6) induced 4-cycles, so f I (n, C 4 ) = 1 2 n 2 + O(n), as observed in [7]. In [11] Győri, Paulos, Salia, Tompkins, and Zamora determined f (n, C 5 ) exactly for all n ≥ 5, and in [7] Ghosh, Győri, Janzer, Paulos, Salia, and Zamora showed that f I (n, C 5 ) = 1 3 n 2 + O(n). In [3] and [4] Cox and Martin determined f (n, H) asymptotically when H is a small even cycle, showing that f (n, C 2k ) = n k k + o(n k ) for k ∈ {3, 4, 5, 6}.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Also, it is straightforward to see that the complete bipartite graph K 2,n−2 contains 1 2 (n 2 − 5n + 6) induced 4-cycles, so f I (n, C 4 ) = 1 2 n 2 + O(n), as observed in [7]. In [11] Győri, Paulos, Salia, Tompkins, and Zamora determined f (n, C 5 ) exactly for all n ≥ 5, and in [7] Ghosh, Győri, Janzer, Paulos, Salia, and Zamora showed that f I (n, C 5 ) = 1 3 n 2 + O(n). In [3] and [4] Cox and Martin determined f (n, H) asymptotically when H is a small even cycle, showing that f (n, C 2k ) = n k k + o(n k ) for k ∈ {3, 4, 5, 6}.…”
Section: Introductionmentioning
confidence: 79%
“…, R t , where R i has boundary uv i wv i+1 , with the addition in the subscript taken modulo t. If at least 7 n 4/5 of these regions have vertices in their interior, then the drawing of G contains a K 2,7 n 4/5 subgraph which does not contain an empty K 2,7 . But G also does not contain a vertex in at most 11 20 n induced 5-cycles, contradicting Lemma 13. So fewer than 7 n 4/5 of the regions have any vertices in their interior. Thus for all but o(n) values of i, none of the regions R i−3 , R i−2 , .…”
Section: Lemma 13 ([7]mentioning
confidence: 87%
See 3 more Smart Citations